Clostridioides Difficile Enteritis: Case Report and Literature Review - Artsiom Klimko; Cristian George Tieranu; Ana-Maria Curte; Carmen Monica Preda; Ioana Tieranu; Andrei Ovidiu Olteanu; Elena Mirela Ionescu (MDPI AG, 2022)
Background: Clostridioides Difficile is a well-known pathogen causing diarrhea of various degrees of severity through associated infectious colitis. However, there have been reports of infectious enteritis mainly in patients with ileostomy, causing dehydration through high-output volume; Case presentation: We report the case of a 46-year-old male patient, malnourished, who presented with high-output ileostomy following a recent hospitalization where he had suffered an ileo-colic resection with ileal and transverse colon double ostomy, for stricturing Crohn's disease. Clostridioides Difficile toxin A was identified in the ileal output confirming the diagnosis of acute enteritis. Treatment with oral Vancomycin was initiated with rapid reduction of the ileostomy output volume; Conclusion: We report a case of Clostridioides Difficile enteral infection as a cause for high-output ileostomy, successfully treated with oral Vancomycin. We also review the existing literature data regarding this specific localized infection.